2013
DOI: 10.11118/actaun201361010059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corn DDGS on broilers performance and meat quality

Abstract: FOLTYN MARIAN, RADA VOJTĚCH, LICHOVNÍKOVÁ MARTINA, DRAČKOVÁ ELIŠKA: Eff ect of corn DDGS on broilers performance and meat quality. Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2013, LXI, No. 1, pp. 59-64 The eff ects of graded levels of corn distillers dried grains with soluble (DDGS) as partial replacement for soybean meal in diets for broilers were observed. In the fi rst experiment 900 males of ROSS 308 were used and they fed diets with 0, 60, 120 and 180 g/kg DDGS in grower di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…In this experiment, increasing inclusion levels of DON-contaminated DDGS in diets decreased L* values of breast meat. Similar results were obtained by Foltyn et al. (2013) who reported that increasing inclusion levels of DDGS in diets decreased breast meat lightness.…”
Section: Discussionsupporting
confidence: 89%
“…In this experiment, increasing inclusion levels of DON-contaminated DDGS in diets decreased L* values of breast meat. Similar results were obtained by Foltyn et al. (2013) who reported that increasing inclusion levels of DDGS in diets decreased breast meat lightness.…”
Section: Discussionsupporting
confidence: 89%
“…The effects of diet based on different sources of vegetable protein as an alternative to the popular SBM on the growth performance and quality of carcasses in broiler chickens have been investigated in many studies [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Another study [52] on the use of peas as a substitute for soybean meal did not show differences in meat traits or growth performance parameters. Laudadio and Tufarelli [34] concluded that WHC, which affects the loss of water from muscles, is an important parameter in defining the quality of meat. Studies by these authors showed that breast and leg muscles from chickens fed on a pea diet were characterized by a higher WHC (19.64% and 24.22%, respectively) as compared with birds fed on soybean meal (17.23% and 15.21%).…”
Section: Chickens' Performance and Meat Qualitymentioning
confidence: 99%
“…The global community is in search of cheap unconventional feed products that would not be inferior in biological value to expensive protein feeds of animal and plant origin and could replace a part of the grain in the diet for the consumption of which poultry competes with humans [6][7][8][9][10][11]. One of the main tasks in the development of the poultry industry is the use of food industry waste and local non-traditional feed, as one of the ways to reduce production costs.…”
Section: Introductionmentioning
confidence: 99%